Leading teachers - Gunter, Helen (London ; New York, NY : Continuum, 2005)
Leading teachers are those who are reseachers and who have developed their pedagogy based on both evidence and conceptually informed practice. This book draws on three important resources: first, case studies of teachers researching and developing practice; second, research evidence on what we know about teacher leadership both nationally and internationally; and, third, models of pedagogy and teacher learning that can support the development of a teacher leadership culture within schools.
Leading Teachers Dimensions of Leading Teachers Leading Teachers as Distributed Leadership Leading Teachers as Researchers Developing Leading Teachers Leading Leading Teachers
Includes bibliographical references and index.
Keywords: School supervision; Educational leadership; Teachers -- Training of